One-pot migration-formylation of benzyl aryl ethers under duff reaction condition - Chavan, Subhash P.; Lasonkar, Pradeep B. (Tetrahedron Letters, 2013)
A one-pot migration-formylation of benzyl aryl ethers under Duff reaction condition is described. The reaction was performed with HMTA (hexamethylene tetramine) and TFA (trifluoroacetic acid). Under the optimal reaction conditions, a variety of Bn and PMB ethers underwent ortho rearrangement. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Benzyl aryl ethers; Duff reaction; Hexamethylene tetramine; One-pot; ortho Rearrangement